2021
DOI: 10.1089/tmj.2020.0222
|View full text |Cite
|
Sign up to set email alerts
|

Change in Ophthalmic Clinicians' Attitudes Toward Telemedicine During the Coronavirus 2019 Pandemic

Abstract: Background: Ophthalmic clinicians report low confidence in telemedicine-based eye care delivery, but it may have changed given its rapid expansion during the coronavirus 2019 (COVID-19) pandemic. Introduction: The purpose of this study was to determine clinician confidence in telemedicine-based eye care services during COVID-19. Materials and Methods: An electronic survey was sent to clinicians at University of Michigan Kellogg Eye Center (April 17, 2020-May 6, 2020) when nonemergent in-person visits and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 10 publications
(11 reference statements)
1
30
0
Order By: Relevance
“…A study at the Kellogg Eye Center at the University of Michigan found that the majority of their ophthalmic clinicians were at least somewhat confident about using telemedicine during the pandemic. 5 Clinicians with high confidence were more likely to use telemedicine and express interest to continue using telemedicine in the future. 5 Thus, cultivating clinician confidence and interest is imperative to further adoption of teleophthalmology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study at the Kellogg Eye Center at the University of Michigan found that the majority of their ophthalmic clinicians were at least somewhat confident about using telemedicine during the pandemic. 5 Clinicians with high confidence were more likely to use telemedicine and express interest to continue using telemedicine in the future. 5 Thus, cultivating clinician confidence and interest is imperative to further adoption of teleophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…5 Clinicians with high confidence were more likely to use telemedicine and express interest to continue using telemedicine in the future. 5 Thus, cultivating clinician confidence and interest is imperative to further adoption of teleophthalmology. At JHM, a substantial proportion of the ophthalmology faculty (58%) completed at least one telemedicine encounter, reflecting a willingness to provide telehealth services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other medical specialties, ophthalmology providers are advised to defer many non-urgent or emergent appointments. Many providers have responded by taking advantage of relaxed regulations on telemedicine by expanding virtual services to maintain relationships with patients and preserve continuity of care rather than canceling appointments outright [28][29][30].…”
Section: Intake Precautionary Measuresmentioning
confidence: 99%
“…This situation applied to eye hospitals too. [ 3 4 5 6 ] Outpatient services dropped by more than 95%, and a significant number of emergency conditions did not receive adequate care. [ 7 8 ] Subsequently, lockdown was eased to some extent from May 4 to May 31 (lockdown III and IV).…”
mentioning
confidence: 99%